IMPLEMENTASI BERBASIS WEB PADA SISTEM INVENTORY GUDANG CHEMICAL PT VICTORY CHINGLUH INDONESIA - Abdurrahman Abdurrahman; Uro Abdulrohim; Lina Marlina (LPPM STMIK BANDUNG, 2022)
The development of technology is growing rapidly, so that the use of information system technology becomes very useful for companies that need accurate, fast, and detailed information. PT Victory Chingluh Indonesia which is engaged in footwear (shoes). This company in inventory management still uses Microsoft Excel and is still a single user so that performance is a bit hampered because the incoming and outgoing goods process only uses records as evidence of taking goods and receiving goods, so that in checking the stock of goods it is still manual and allows there to be data that does not match. So that it can cause slow in the search for goods and slow down in making reports. So to overcome this, a computerized system is needed. This system is designed using the UML (Unified Method Language) method. Programming language using HTML, PHP, and MySQL database. Based on the analysis of the problem, the results obtained are that this inventory system can provide information that is accessed by the admin and head of the warehouse. Admin can add, change, and delete and print goods data reports, incoming and outgoing goods. Meanwhile, periodic checks and print reports can be done by the head of the warehouse. This inventory system was created to make it easier for companies to manage stock of goods and provide information more quickly. This application can perform data searches automatically, record incoming goods and outgoing goods, and can make reports of incoming goods and outgoing goods.